Histological features of peritoneal lavage with ropivacaine in rats with fecal peritonitis - Brocco,Marcos Célio (2012)
PURPOSE: To evaluate the histological features in lungs, peritoneum and liver of rats subjected to fecal peritonitis and treated with peritoneal lavage with 0.2% ropivacaine. METHODS: Twenty Wistar rats were subjected to laparotomy 6 h after the fecal peritonitis induction with autogenous stool. Rats were randomly distributed into 4 groups: I - (n=5) Control, no treatment; II - (n=5) Drying of the abdominal cavity; III - (n=5) Abdominal cavity lavage with 3 ml 0.9% saline solution and drying; and IV - (n=5) Abdominal cavity lavage with 3 ml 0.2% ropivacaine and drying. The animals that died underwent necropsy, and the surviving ones were subjected to euthanasia on the 11th day post-surgery. Fragments of liver, lungs and peritoneum were removed for histological evaluation. RESULTS: The animals that received peritoneal lavage (groups III and IV) showed greater survival than the drying and control groups. Lavage with ropivacaine prevented death during the observed period. Peritoneal lavage with ropivacaine maintained the architecture of the lung, peritoneum and liver without any important histological alterations. The histopathological findings analyzed correlated with greater survival of group IV. CONCLUSION: Treatment of fecal peritonitis in rats with peritoneal lavage using 0.2% ropivacaine demonstrated a reduction in histopathological alterations related to inflammatory response and sepsis.